3D architectured air sensing tubes for a portable mechanical ventilator. (3rd September 2021) - Kim, Tae-Ho; Min, Xin; Baker, Daina; Lee, Wonchul; Kim, Woo Soo
Abstract: Today, respiratory ventilators are in high demand at the peak of the COVID-19 outbreak. However, there are concerns regarding insufficient supply of ventilators to handle the impending surge due to the high cost, and slow production and deliveries. Thus, the development of a low-cost portable ventilator becomes essential. The mechanical ventilator requires two main components including an active airbag and its venting control system. We developed a reliable active airbag designed with mechanically tunable 3D origami structures. The 3D origami structure based active airbag demonstrates reliable and reconfigurable characteristics. The active airbag's volume can be tuned by controlling the triangular angles in the 3D origami-folding plates. Moreover, its volumetric ratio before and after compression is around 85%. Also, the rotating behavior of 3D origami tube under the compressive force allows more functionalities in the airbag such as the architectured pressure sensing. The 3D printed origami sensor measures the compressed angle to confirm the accuracy of detected pressure in the ventilator circuit. We achieved accurate delivery of targeted air volume with specific airflow rate by 3D printed reconfigurable origami tubes.